Do public and internal debt cause income inequality? Evidence from Kenya - Wilkista Obiero; Seher Gulsah Topuz (Journal of Economics, Finance and Administrative Science, 2021)
Purpose - This study aims to determine whether there is an effect of internal and public debt on income inequality in Kenya for the period 1970-2018. Design/methodology/approach The relationship is examined by using the Autoregressive Distributed Lag (ARDL) model by Pesaran et al. (2001) and Toda Yamamoto causality by Toda and Yamamoto (1995). Findings Our findings suggest that both internal and public debt harm inequality in Kenya in the long term. Furthermore, a one-way causality from internal debt to income inequality is also obtained while no causality relationship is found to exist between public debt and income inequality. Based on these findings, the study recommends that to reduce income inequality levels in Kenya, other methods of financing other than debt financing should be preferred because debt financing is not pro-poor. Originality/value This study is unique based on the fact that no previous paper has analysed the debt and inequality relationship in Kenya. To the best of our knowledge, this will be the first study to analyse the applicability of redistribution effect of debt in Kenya. The study is also different in that it provides separate analysis for public debt and internal debt on their effects on income inequality.
Keywords: D31; E24; H63; 330; Income inequality; Income redistribution; Internal debt; Public debt